Home care utilization and costs in stage IV lung cancer: a Canadian public payer experience. (December 2014) - Mittmann, Nicole; Seung, Soo Jin; Liu, Ning; Porter, Joan; Leighl, Natasha; Trudeau, Maureen; Evans, William K; Earle, Craig
SUMMARY : Background: Lung cancer (LC) is a leading cause of morbidity and mortality and there is limited information on the type, quantity and cost of home care services (HCS) for LC.Aim: The objectives of this study include: identifying a stage IV LC cohort; determining the utilization and costs of HCS for the stage IV LC cohort; and comparing HCS utilization and costs by phase of disease.Methods: New cases of stage IV LC were extracted from a provincial cancer registry and linked to administrative datasets. HCS utilization and costs (2009 Canadian dollars [CAD]) for stage IV cases were determined from a public payer perspective and by disease phase.Results: There are 4616 stage IV LC patients who used HCS.. The mean number of HCS visits per 30 days was 7.7 and the mean cost per 30 days was CAD$798 for terminal-phase patients.Conclusion: HCS costs for stage IV patients are less expensive than other health resources.